2017
DOI: 10.1111/asj.12875
|View full text |Cite
|
Sign up to set email alerts
|

Different thermotolerances in in vitro‐produced embryos derived from different maternal and paternal genetic backgrounds

Abstract: The present study evaluated the effects of genetic backgrounds on the developmental competence and thermotolerance of bovine in vitro-produced (IVP) embryos. First, Holstein (Hol) and Japanese Black (JB) oocytes were fertilized with sperm from Hol, JB and a thermotolerant breed (Brahman), and in vitro development was evaluated when the embryos were exposed to heat shock on Day 2 (Day 0 = day of fertilization). Sperm genetic backgrounds affected the developmental competence in controls (P < 0.05). Second, the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
(51 reference statements)
0
5
0
Order By: Relevance
“…It has been reported that any source of stress, including HS, has the potential to disrupt the process of interactions between the uterus and the embryo (Thatcher, Meyer, & Danet-Desnoyers, 1995), consequently compromising the establishment and maintenance of pregnancy. Although some studies have shown heat-shocked bovine embryos have the competence and establish pregnancy (Khatun et al, 2018;Sakatani, Yamanaka, Balboula, & Takahashi, 2017), it is evident HS influences embryo development. Also, an in vitro model of bovine embryo production has been used to mimic HS on lactating dairy cows during summer days (Nabenishi et al, 2011(Nabenishi et al, , 2012.…”
mentioning
confidence: 98%
“…It has been reported that any source of stress, including HS, has the potential to disrupt the process of interactions between the uterus and the embryo (Thatcher, Meyer, & Danet-Desnoyers, 1995), consequently compromising the establishment and maintenance of pregnancy. Although some studies have shown heat-shocked bovine embryos have the competence and establish pregnancy (Khatun et al, 2018;Sakatani, Yamanaka, Balboula, & Takahashi, 2017), it is evident HS influences embryo development. Also, an in vitro model of bovine embryo production has been used to mimic HS on lactating dairy cows during summer days (Nabenishi et al, 2011(Nabenishi et al, , 2012.…”
mentioning
confidence: 98%
“…The lower lipid peroxide end product (i.e., MDA) and the higher GSH levels could probably be interpreted by a direct and/or an indirect antioxidant action of melatonin. Especially, glutathione, a scavenger of H 2 O 2 , is the major antioxidant component for scavenging ROS at oocyte level [7] and exerts a crucial role in embryonic developmental competence at preimplantation stages. When glutathione is added in IVM culture medium, the in vitro tolerance of bovine embryos to heat stress at 42 • C is increased [40].…”
Section: Discussionmentioning
confidence: 99%
“…Almost all the reproductive processes, from the stage of follicular growth and oocyte maturation to parturition, as well as lactation and uterus involution, could be affected by heat stress. However, in farm animals the principal adverse effect of heat stress on reproduction is the low fertility rate, mainly due to high susceptibility of preovulatory follicles and of preimplantation stage embryos to high maternal temperature [6,7]. The early developmental stages from oocytes to cleavage-stage are thermosensitive, while advanced developmental stages of early embryos, such as morulae and blastocysts are thermotolerant.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During summers, a negative energy balance is caused by a decrease in feed intake. As a result, steroid metabolism, which controls sex hormone secretion, is adversely affected, causing ovarian dysfunction [ 12 , 14 , 15 , 16 ]. Breeding of cattle is mostly carried out by artificial insemination (AI) in Japan.…”
Section: Decline In Livestock Fertility and Global Warmingmentioning
confidence: 99%